Maternal Sense of Control During Childbirth and Infant Feeding Method. Issue 3 (March 2020) - Dude, Annie; Fette, Lida M.; Reddy, Uma M.; Tita, Alan T.N.; Silver, Robert M.; El-Sayed, Yasser Y.; Wapner, Ronald J.; Rouse, Dwight J.; Saade, George R.; Thorp, John M.; Chauhan, Suneet P.; Iams, Jay D.; et al.
Abstract : OBJECTIVE: To estimate whether maternal sense of control in labor is associated with breastfeeding at 4–8 weeks postpartum. METHODS: This is a secondary analysis of data from a multicenter randomized controlled trial of elective induction of labor at 39 weeks of gestation in low-risk nulliparous women. In this trial, women completed the Labor Agentry Scale, a validated measure of women's feelings of control over the childbirth process, 6–96 hours after delivery. The Labor Agentry Scale score, which is higher with more perceived control during childbirth, was analyzed both as a continuous and a categorical variable (quintiles). Self-reported breastfeeding at 4–8 weeks postpartum was categorized as exclusive breastfeeding, breastfeeding and formula feeding, or exclusive formula feeding. Women were included in this analysis if they labored, filled out a Labor Agentry Scale questionnaire, had a neonate who survived until the postpartum visit, and provided information on infant feeding. Multinomial logistic regression was used to adjust for confounders. RESULTS: Of 5, 185 women, 32.9% (n=1, 705) were exclusively breastfeeding, 31.2% (n=1, 620) were breastfeeding and formula feeding, and 35.9% (n=1, 860) were exclusively formula feeding 4–8 weeks after delivery. Overall Labor Agentry Scale score ranged from 34 to 203 (median 167, interquartile range 145–182). The median Labor Agentry Scale score was 169 (interquartile range 151–183) for women exclusively breastfeeding, 166 (interquartile range 142–182) for women who were breastfeeding and formula feeding, and 164 (interquartile range 142–181) for women who were only formula feeding ( P <.001). In the unadjusted multinomial model, women with Labor Agentry Scale scores in the lowest two quintiles (ie, those with lower perceived control during childbirth) were less likely to be exclusively breastfeeding (as compared with those exclusively formula feeding) than women in the highest Labor Agentry Scale quintile. When controlling for confounders, however, this association was no longer significant. CONCLUSION: After adjustment for confounders, perceived control during childbirth was not associated with breastfeeding at 4–8 weeks postpartum among nulliparous women. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01990612. Abstract : Maternal perception of control during childbirth is not associated with breastfeeding at 4–8 weeks postpartum.